Pancreatic intraductal papillary mucinous neoplasm: where is the challenge? - Fritz, Stefan; Hackert, Thilo; Büchler, Markus W. (Digestive diseases, 2015)
Cystic lesions of the pancreas are increasingly recognized due to the widespread use of modern abdominal imaging technologies. The majority of these lesions display pseudocysts and mucinous cystic neoplasms. In contrast to pseudocysts, it is well established that mucinous cystic neoplasms of the pancreas exhibit a significant potential for malignant transformation over time. Among mucinous cystic tumors, the most frequently observed entity is pancreatic intraductal papillary mucinous neoplasm (IPMN). IPMNs are characterized by cystic dilation of pancreatic ducts and the production of mucus and by an adenoma-carcinoma sequence eventually culminating in invasive carcinoma in some patients. Due to the high risk of harboring malignancy, there is international consensus that IPMNs with involvement of the main pancreatic duct should be recommended for surgical resection. To date, the indication for surgery of branch-duct IPMNs is controversially discussed because of the overall lower risk of malignant transformation compared to main-duct IPMNs. Particularly for small and asymptomatic side-branch IPMNs, the indication for surgical resection remains challenging. In addition to the international consensus guidelines, a number of potential preoperative features predicting malignant transformation have been discussed recently. Moreover, novel surgical pancreatic parenchyma-sparing techniques such as enucleations or segmental pancreatic resections have been reported in order to treat IPMNs. The present article aims to demonstrate the current scientific knowledge in this field and to highlight the current controversy.
Published online: December 17, 2014
Gesehen am 16.06.2020